Sexual abuse victim empowerment programme : an archival study assessing the relationship between demographics and level of intellectual functioning - Todd, Roxanne Margaret June (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MA (Psychology))--University of Stellenbosch, 2005.